Political legitimacy based on religion: An analysis of sociological religion in Jambi local democracy 2024 - Halim, Abdul; Kusnadi, Edy; Surbakti, Junita; Ermawati, Ermawati; Mubarak, Zaki (Trigin Publisher, 2025)
In Indonesia, religion has long been a major factor in determining political legitimacy, especially when it comes to local democracy. This study looks at how political actors in Jambi harness religious symbols, moral authority, and religious leaders' power to win over voters. The goal is to comprehend religion as a strategic sociopolitical tool ingrained in regional power dynamics rather than just as a set of beliefs. The study employs a qualitative research design and examines how religious narratives and practices function within electoral rivalry through participant observation, in-depth interviews, and document analysis. The results show that religion serves as symbolic capital (Bourdieu) that can be converted into political capital, opening doors for legitimacy based on Weber's conception of conventional and charismatic authority. Voter turnout, candidate credibility, and public trust have all been demonstrated to be greatly increased by religion-based tactics. However, the public's reaction to these methods is similarly conflicted. Religious participation promotes social cohesiveness and moral resonance in political discourse, but it also bears the risk of social polarization and identity exclusivism, which could jeopardize the stability and inclusivity necessary for democratic consolidation. The study comes to the conclusion that religion functions as a dual-force legitimacy mechanism, supporting social integration and political leadership while simultaneously fostering factionalism in multiple communities. The ramifications highlight the need for a more critical view of religion's involvement in electoral politics, acknowledging it as a formidable tool for political mobilization as well as a possible obstacle to the growth of an inclusive and developed local democracy in Indonesia.